Reconstructing Ukraine creating a freer, more prosperous and secure future - Shatz, Howard J. 1960-; Tarini, Gabrielle; Ries, Charles P. 1951-; Dobbins, James 1942-2023 (RAND Corporation, 2023)
The post-war reconstruction effort in Ukraine might be the largest post-war rebuilding effort in modern history. Both the United States and Europe have begun to plan for Ukraine's success. The authors of this report examine previous post-war and post-natural disaster reform and reconstruction efforts to draw lessons and inform policymakers. They also discuss security arrangements, which will be essential for the success of reconstruction. While reconstruction in Iraq and Afghanistan was more recent, Ukraine is fundamentally different. Instead, more-relevant lessons can be drawn from the truly transformative reform and reconstruction efforts in Western Europe following World War II, Central and Eastern Europe following the Cold War, and the Western Balkans following the wars in the former Yugoslavia. In all of these cases, the United States provided seed money and security, and the Europeans provided the bulk of the funding and advanced the process of European integration
Keywords: Geschichte 1945-; Internationale Kooperation; Nachkriegszeit; Wiederaufbau; Ukraine; Postwar reconstruction / Ukraine / International cooperation / Planning; Ukraine Conflict, 2014-; Ukraine / History / Russian Invasion, 2022-